Effects of Lactobacillus casei and Aggregatibactor actinomycetemcomitans against Streptococcus mutans according to the Concentration of Sucrose - Soon-Jeong Jeong (치위생과학회지, 2023)
Background: Some studies confirm the reduction of the number of Streptococcus mutans in saliva and dental plaque by Lactobacillus, however, these effects are not always confirmed in in vitro and clinical studies, and only the risk of dental caries has been reported. Our in vitro study aimed to reveal microbial and biochemical changes in the single cultures of S. mutans, Lactobacillus casei and Aggregatibactor actinomycetemcomitans and co-cultures of S. mutans and L. casei or A. actinomycetemcomitans according to sucrose concentration. We also aimed to confirm the anti-oral bacterial and anti-biofilm activities of L. casei and A. actinomycetemcomitans against S. mutans according to sucrose concentration. Methods: S. mutans (KCCM 40105), L. casei (KCCM 12452), and A. actinomycetemcomitans (KCTC 2581) diluted to 5×106 CFU/ml were single cultured, and L. casei or A. actinomycetemcomitans applied at concentrations of 10%, 20%, 30% and 40% to S. mutans were co-cultured with selective medium containing 0%, 1% and 5% sucrose at 36.5°C for 24 hours. Measurements of bacterial growth value and acid production, disk diffusion and biofilm formation assays were performed. Results: In the medium containing sucrose, the bacterial growth and biofilm formation by S. mutans, L. casei, and A. actinomycetemcomitans were increased. In contrast, 30% and 40% of L. casei in the medium containing 0% sucrose showed both anti-oral bacterial and anti-biofilm activities. This implies that L. casei can be used as probiotic therapy to reduce S. mutans in a 0% sucrose environment. Conclusion: The concentration of sucrose in the oral environment is important for the control of pathogenic bacteria that cause dental caries and periodontitis. To apply probiotic therapy using L. casei for S. mutans reduction, the concentration of sucrose must be considered.